Скандинавские просодемы - Кузьменко, Ю. К. (Kalbotyra, 1985)
The function and phonetic properties of the Scandinavian prosodemes depend on the syllable structure of a language. In those Scandinavian dialects where the moracounting is preserved the tonal distinctions appear to be moric peak accents. In the most Scandinavian dialects and, in standard Swedish and Norwegian (in its both variants) the syllable type being V̄Č ∼ V̆C̄ with interdependence between vowel and consonant length. The tonal and dynamic distinctions here have become syllable accents. The syllable structure of Danish resembles that of the West Germanic languages. The stød in Danish is neither a moric nor a syllable accent but a device which enables one to distinguish four types of contact. The Danish “accent” stud is no more a suprasegmental unit but a device of segmental prosodics. In some Danish dialects the apocope took place, which changed their type into morphosyllabic. Prosodic characteristics function here as tones like those in morphosyllabic languages of the Chinese type.Thus the function of prosodic features is determined by the syllable structure of the language.